Enabling seamless investigation of fast and complex flow fields in microfluidics via metal lead halide perovskite based micro-particles - Huang, Yi (2023)
Critical to both fundamental fluid physics and practical applications in microfluidics is the quantitative velocity field distribution for which micro particle image velocimetry (µ-PIV) has been a major measurement technology. Yet, the achievable imaging speed from a benchmark µ-PIV system is limited by the low fluorescence intensity of conventionally used fluorescent microparticles, restricting the capture of detailed flow field information in fast microfluidic processes. We tackle this hurdle by developing highly fluorescent micro particles from halide perovskite quantum dots by a generic one-step approach. This novel self-assemble method makes the fluorescent micro particles resistant to the aggregation induced quenching effect and ensures high luminescence efficiency, such that a record fluorescent imaging speed of 100,000 frames per second under the illumination of a low power continuous wave (CW) laser is achieved. Our finding not only offers the opportunity of affordable high performance µ-PIV but also allows for the seamless exploration of fast and complex microscale flow fields such as droplet dynamics and complex emulsion processes inaccessible by using conventional dye-based luminescent tracers. Besides the flow tracers in µ-PIV, such general and novel self-assembled micro particles may also find far reaching applications in other imaging related venues.